If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = -8c + 9c Combine like terms: -8c + 9c = 1c 16 = 1c Solving 16 = 1c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 16 + -1c = 1c + -1c Combine like terms: 1c + -1c = 0 16 + -1c = 0 Add '-16' to each side of the equation. 16 + -16 + -1c = 0 + -16 Combine like terms: 16 + -16 = 0 0 + -1c = 0 + -16 -1c = 0 + -16 Combine like terms: 0 + -16 = -16 -1c = -16 Divide each side by '-1'. c = 16 Simplifying c = 16
| (9x+2)(9x-1)=9x^2+3x-2 | | Y=0(-3)+-4 | | 5(5x-6)=67.5 | | 3x^2+15x+30= | | 8(n+1)-1=3(8+3n)-3 | | -x-13=-31 | | -6=3u4+12 | | y=4(-3)+3 | | 3x^2+15x+25= | | -6x^2-20x+16=0 | | (9x+2)(9x-1)=x | | 3x-17=x-1 | | 16x^4-64=0 | | 2x+11=43-3x | | 15-2(4)= | | 4n+12=4n+12 | | h+11.3=-11.3 | | 15-2(2)= | | 3x-5=72 | | a(n+1)= | | h=-8t^2+63 | | F(x)=62+35log(11-4) | | 12x+3=32 | | -6+2(10)= | | 0.6x-14=0.4x | | f(x)=9x^2+3x-2 | | 9x+3y-36=0 | | -6+2(2)= | | 9x^4+9x=0 | | 2h=-16t^2+126t | | 2(15)-15= | | 2(9)-15= |